The Comparison of Students' Perceived Levels of Self-Efficacy in Live, Online and Live Online Courses - Wangwongwiroj, Tarosh; Yasri, Pratchayapong (International Journal of Research in STEM Education, 2021)
Education during COVID-19 pandemic has been greatly disrupted. While live courses where students meet face-to-face in classrooms are physically limited, online courses become more popular where students learn from pre-recorded videos at their own pace. In contrast, live online courses are learning modes where students and teachers meet via webinar tools such as zoom, skype, google meet, webex, teams, to name a few. This study compared students' perceived levels of self-efficacy in these three different settings. Self-efficacy is defined as belief in one'own ability to accomplish a task, which can be influenced by mastery experiences, verbal persuasion, vicarious experiences, and physiological states. An online questionnaire with 12 closed-ended statements based on a 5-Likert scale was developed, representing the four factors in the three modes of learning. A total of 105 voluntary responses were received. Statistical differences in the mean scores were determined by a paired sample t-test. The results at the significance level of 95% showed that the mean score of mastery experiences was the greatest in live courses (4.5), followed by live online (4.4) and online courses (3.3). The same was observed in vicarious experiences where live courses gained the greatest mean (4.5), followed by live online (4.3) and online courses (1.7). The means of verbal persuasion between live (4.5) and live online courses (4.3) did not differ significantly, but the lowest was in online courses (1.6). Interestingly, the reverse trend was found in psychological states in which the greatest was found in online (4.7), followed by live online (4.5) and live courses (3.6). The analysis above was based upon students who had no technical difficulties to access live online courses. However, this may not be applicable to contexts where internet connect is problematic. For educational implications, the findings revealed that live online courses are proven to be the most appropriate mode of learning during the pandemic. In contrast, online courses are associated with lower levels of mastery experiences, vicarious experiences, and verbal persuasion perceived by learners; whereas live courses lowered psychological states.